Nest - a new domestic landscape re.visited - Costa, Carlos Casimiro da (2013)
NEST (natural/nano Energy System Technology) project design refocus in a revalidation to the exposition fixed in 1972 in MOMA, New York by Emilio Ambasz. This exposition give us a twist radical orientation proposing in that particular time new paths concerning ecological perspectives, confronting the standard mainstream, and proposing new systems to live. Design approach needs to recover these symptoms melted in time, proposing adaptable systems to different cultures and meaning in a cultural twist paradigm. For that motive is our intention to readapt thoughts and process of thinking that was intentionally collapsed in a past domestic landscape.